The Cross-Border Transplantation of Variable Universal Life Insurance: The Evolution and the Regulatory Challenges - Xingxing Li (Washington University Global Studies Law Review, 2021)
Variable universal life insurance, a financial instrument blending in features of both a conventional insurance policy and a securities product, has a long history in sophisticated financial markets such as the United States, yet is new to China’s financial system. The variable insurance made in China serves different business purposes than its U.S. counterparts. Notably, it played a salient role as a financing instrument for the hostile bidder in the landmark Baoneng/Vanke hostile takeover attempt. It results in distinctive financial risks emerging from China’s regulation institution. Drawing contrast to the United States and employing theories on the economic analysis of regulation, this article examines the previous and current regulatory approaches toward the Chinese version of variable insurance and criticizes the disoriented regulation philosophy. It argues that the newly promulgated Asset Management Rules are not helpful in recognizing the securities feature embedded in variable insurance, nor do they optimally mitigate the financial risks associated with variable insurance. The policymakers have yet to balance the freedom of financial innovation with the regulation of the financial market. As a result, the regulators would have to sacrifice either the proper functioning of variable insurance or the stability of the financial system.
Keywords: variable universal life insurance; regulatory arbitrage; functional regulation; functional convergence of financial products; unit investment trust; China; United States